Flurbiprofen benzyl nitrate (NBS-242) inhibits the growth of A-431 human epidermoid carcinoma cells and targets ß-catenin - Nath N; Liu X; Jacobs L; Kashfi K (Dove Medical Press, 2013)
Niharika Nath,1,2 Xiaoping Liu,3 Lloydine Jacobs,1 Khosrow Kashfi1,3 1Department of Physiology, Pharmacology, and Neuroscience, Sophie Davis School of Biomedical Education, City University of New York Medical School, New York, NY, USA; 2Department of Life Sciences, New York Institute of Technology, New York, NY, USA; 3Division of Cancer Prevention, Department of Medicine, Stony Brook University, Stony Brook, NY, USA Background: The Wnt/ß-catenin/T cell factor (TCF) signaling pathway is important in the development of nonmelanoma skin cancers (NMSCs). Nitric-oxide-releasing nonsteroidal anti-inflammatory drugs (NO-NSAIDs) are chemopreventive agents consisting of a traditional NSAID attached to an NO-releasing moiety through a chemical spacer. Previously we showed that an aromatic spacer enhanced the potency of a particular NO-NSAID compared to an aliphatic spacer. Methods: We synthesized an NO-releasing NSAID with an aromatic spacer (flurbiprofen benzyl nitrate, NBS-242), and using the human skin cancer cell line A-431, we evaluated its effects on cell kinetics, Wnt/ß-catenin, cyclin D1, and caspase-3. Results: NBS-242 inhibited the growth of A-431 cancer cells, being ~15-fold more potent than flurbiprofen and up to 5-fold more potent than NO-flurbiprofen with an aliphatic spacer, the half maximal inhibitory concentrations (IC50) for growth inhibition being 60 ± 4 µM, 320 ± 20 µM, and 880 ± 65 µM for NBS-242, NO-flurbiprofen, and flurbiprofen, respectively. This effect was associated with inhibition of proliferation, accumulation of cells in the G0/G1 phase of the cell cycle, and an increase in apoptotic cell population. NBS-242 cleaved ß-catenin both in the cytoplasm and the nucleus of A-431 cells. NBS-242 activated caspase-3 whose activation was reflected in the cleavage of procaspase-3. To test the functional consequence of ß-catenin cleavage, we determined the expression of cyclin D1, a Wnt-response gene. NBS-242 reduced cyclin D1 levels in a concentration dependent manner. Conclusion: These findings establish a strong inhibitory effect of NBS-242 in A-431 human epidermoid carcinoma cells. NBS-242 modulates parameters that are important in determining cellular mass. Keywords: flurbiprofen, nitric oxide, ß-catenin, chemoprevention, skin cancer